Ultrasound assessment of fascial connectivity in the lower limb during maximal cervical flexion: technical aspects and practical application of automatic tracking.. - Cruz-Montecinos, Carlos; Cerda, Mauricio; Sanzana-Cuche, Rodolfo; Martín-Martín, Jaime; Cuesta-Vargas, Antonio (Springer Nature, 2016)
This study aimed to evaluate the displacement of the medial gastrocnemius fascia during cervical spine flexion in a kyphotic posture with knees extended and ankles at 90°. The study used ultrasound recording and the Lucas-Kanade iterated pyramid (LKP) algorithm to track fascia displacement. The results showed that 66% of the subjects had a displacement of the proximal fascial tissue above the basal error. The onset of fascial displacement during cervical spine flexion was detected in 70% of the cycle, but only when detected for more than 80% of the cycle was the displacement considered statistically significant. The study concludes that there is a statistically significant displacement of the deep fascia, as measured by the automated tracking method. However, further studies are needed to fully understand the mechanisms associated with these results.
Keywords: Fascia; Cervicalgia; Connective tissue; Myofascial; Rehabilitation; Tracking motion